FORMATION OF RESPONSIBILITY IN HIGHER EDUCATION STUDENTS FOR EDUCATIONAL ACTIVITIES - Muhammamadiyeva Manzura Maratovna (American Journals, 2023)
In this article, the role and importance of the formation of students' responsibility for educational activities, the levels of learning in the field of educational process and the development of educational activity, mental cognitive activity - targeting the areas of motivation, value and need. The importance of influence and the opinions about the impact of the activities of advanced teachers in the formation of students' responsibility for educational activities are scientifically stated. For example, as a result of mastering aspects of the formation of responsibility for educational activities, the main factors, conditions and opportunities that directly affect its development are discussed. The positive possibilities of forming students' responsibility towards educational activities have been scientifically and pedagogically analyzed.
Keywords: Student, learning, responsibility, efficiency, duty, mission, value, activity, management, development.